Exposição de fibroblastos provenientes de pterígios recidivados e da cápsula de Tenon normal ao tacrolimus (FK-506) - de Carvalho, Clodomir S.C. [UNESP]; Viveiros, Magda Massae Hata [UNESP]; Schellini, Silvana Artioli [UNESP]; Candeias, João Manoel Grisi [UNESP]; Padovani, Carlos Roberto [UNESP] (My University, 2007)
Purpose: To evaluate fibroblast proliferation activity of normal Tenon's capsule and of recurrent pterygia exposed in vitro to tacrolimus (FK506). Methods: A randomized prospective study was performed with 8 samples of recurrent pterygia and 6 samples of normal Tenon's capsule from the same patient with pterygium at the Faculdade de Medicina de Botucatu - UNESP. The samples were cultivated and exposed once to 1M tacrolimus (FK 506) and the proliferation rate was evaluated 1, 5, 12 and 19 days after the exposure. The data were statistically analyzed. Results: The fibroblasts from pterygia exposed in vitro to tacrolimus had a significantly lower proliferation rate than controls after one day of exposure (p<0.05). Nineteen days after exposure to tacrolimus, exposed cells proliferated more than the non-exposed. Conclusion: Tacrolimus is effective to inhibit proliferation of Tenon's capsule fibroblasts from pterygia one day after exposure. Further studies are needed to define the role of tacrolimus in pterygium treatment.
Fibroblasts from recurrent pterygium and normal Tenon's capsule exposed to tacrolimus (FK-506)
Keywords: Cell culture techniques; Cell proliferation; Fibroblasts/pathology; Pterygium/pathology; Recurrence; Tacrolimus/therapeutic use